2021
DOI: 10.1080/1046560x.2020.1827190
|View full text |Cite
|
Sign up to set email alerts
|

Developing Instructional Materials Aligned to the Next Generation Science Standards for All Students, Including English Learners

Abstract: The adoption of A Framework for K-12 Science Education and the Next Generation Science Standards (NGSS) across the U.S. requires that the field of science education develops high-quality instructional materials. This need is particularly urgent as schools and districts are expected to design or adapt instructional materials for an increasingly diverse student population. In this article, we present our conceptual approach for developing yearlong fifth-grade NGSS-aligned instructional materials with a focus on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 27 publications
0
34
0
Order By: Relevance
“…One of the first of these ideas incorporated into several new investigations focuses on the need for meaningful science learning for all students, especially for those marginalized, underrepresented groups in the United States, where historical and cultural identity are often ignored in science textbooks, instructional materials, and pedagogical practices (Lee et al, 2019). Many recent studies focus on these ideas by strengthening learners’ identity formation (Jagers et al, 2019), engaging students in sensemaking from collective experiences (Easley, 2020), building collaborative experiential science activities (Baser et al, 2017), intersecting science learning with other disciplines (Arias et al, 2016; Fitzgerald, 2020), and providing equitable learning opportunities (Haas et al, 2021; Pinkard et al, 2017). Although they often have similar and overlapping goals, the research approach and methods for evaluating the impact of the various interventions among these studies differ.…”
Section: Theoretical Framing Of the Ml-pbl Interventionmentioning
confidence: 99%
“…One of the first of these ideas incorporated into several new investigations focuses on the need for meaningful science learning for all students, especially for those marginalized, underrepresented groups in the United States, where historical and cultural identity are often ignored in science textbooks, instructional materials, and pedagogical practices (Lee et al, 2019). Many recent studies focus on these ideas by strengthening learners’ identity formation (Jagers et al, 2019), engaging students in sensemaking from collective experiences (Easley, 2020), building collaborative experiential science activities (Baser et al, 2017), intersecting science learning with other disciplines (Arias et al, 2016; Fitzgerald, 2020), and providing equitable learning opportunities (Haas et al, 2021; Pinkard et al, 2017). Although they often have similar and overlapping goals, the research approach and methods for evaluating the impact of the various interventions among these studies differ.…”
Section: Theoretical Framing Of the Ml-pbl Interventionmentioning
confidence: 99%
“…As a prominent inquiry‐based learning approach, PBL has received wide attention in science education as an instructional approach to designing optimal learning environments (e.g., Craig & Marshall, 2019; Haas et al, 2021; Han et al, 2015; Schneider et al, 2022; Zhao & Wang, 2022). In addition to the above features, PBL also encompasses the aim of including sustainable and coherent features to support students' science proficiency development (e.g., Fortus et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed the development process of instructional materials based on the NGSS, focusing on equity. For example, Hass et al [48] presented the conceptual framework focused on equity that guided the development of NGSS-aligned instructional materials for the fifth grade with a focus on English learners. The authors unpacked a target set of performance expectations in terms of the specific elements of the three dimensions of the NGSS.…”
Section: Discussionmentioning
confidence: 99%
“…However, the authors agreed that there are still tensions in developing new teaching materials to address the equity issues. Hass et al [48] mentioned that addressing all three dimensions of each performance expectation would be a challenge. Another tension involves capitalizing on students' everyday experiences across various places within and across formal and informal settings [50].…”
Section: Discussionmentioning
confidence: 99%